Analysis Of The Effect Of Bending Strength On Scaffolding System With Direct Analysis Method - Michael Talim (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2021)
Steel scaffolding is a very important component in formwork work to support further work. The purpose of this analysis is to review the maximum compressive strength that occurs in 3-story scaffolding before buckling occurs using the direct analysis method (DAM). The design of steel structures, which are generally slender, requires stability analysis. The result is influenced by imperfections (non-linear geometry) and inelastic conditions (non-linear material). In this final project, we use second-order inelastic analysis based on direct analysis method. The 3-level scaffolding model was analyzed using beam elements in the SAP2000 program with 6 variations of notional loads applied to the weak axis direction of the scaffolding pipe.The lowest compressive strength on 3-story scaffolding before buckling occurs is 18.24 kN with horizontal notional loads to the right on the first level scaffolding, left on the second level scaffolding and to the right on the 3rd level scaffolding. The results of the analysis show that the maximum compressive strength obtained results in a large displacement drastically in the iteration step. By using the analysis on the DAM method, the results obtained are more effective.